Environmental impact-economic factors on the intensification of land use - ЧЕРЕВКО, І. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy)
Тhe current problems of the impact of ecological and economic factors on the intensification of land resources use, and economic measures considering the location of agricultural production as well as their suitability for growing crops ave considered.